Tourism Development of Russian Territories: Competitiveness, Effectiveness and Sustainability - MOROZOV, Mikhail A.; MOROZOVA, Natalya S.; BELYANSKIY, Vladimir; BELYANSKAYA, Olga; YUDINA, Tatiana (Journal of Environmental Management and Tourism, 2017)
The purpose of the article is to development a theoretical concept of specialization of Russian territories on the tourist activities and to offer practical recommendations for development of tourism in Russia’s industrial territories in the interests of their sustainable development, support for competitiveness, and high effectiveness. The authors use the methods of systemic, structural and functional, comparative, and problem analysis, analysis of causal connections, synthesis, induction, deduction, visualization, etc. The authors view perspectives and determine the possibilities for re-orientation of modern Russia’s territories for tourism and determine the corresponding preconditions. Also, the advantages of tourist development of territories, as compared to the industrial specialization, are determined, as well as the problems on the way of industrially-oriented territories’ transition to tourist specialization. As a result, it is concluded that modern Russia has a large potential in the sphere of the tourism sector development, which is interesting from the point of view of increase of competitiveness and effectiveness of territorial economy and achievement of its sustainable development. Due to low market barriers and close connections to other sphere of economy, the tourist sector opens wide perspectives for restoration of business activity in crisis-influenced industrial regions of Russia.